Exacerbation of Allergic Airway Inflammation in Mice Lacking ECTO-5′-Nucleotidase (CD73) - Caiazzo, Elisabetta; Cerqua, Ida; Riemma, Maria Antonietta; Turiello, Roberta; Ialenti, Armando; Schrader, Jurgen; Fiume, Giuseppe; Caiazza, Carmen; Roviezzo, Fiorentina; Morello, Silvana; Cicala, Carla (Frontiers in Pharmacology, 2020)
Airways is a target organ of type I allergy and atopy is the main aetiological factor of bronchial asthma. Predisposition to allergy and individual response to allergens are dependent upon environmental and host factors. Early studies performed to clarify the role of extracellular adenosine in airways highlighted the importance of adenosine-generating enzymes CD73, together with CD39, as an innate protection system against lung injury. In experimental animals, deletion of CD73 has been associated to immune and autoimmune diseases. Our experiments have been performed to investigate the role of CD73 in the assessment of allergic airway inflammation, following sensitization. We found that in CD73-/- mice sensitization, induced by subcutaneous ovalbumin (OVA) administration, develops with increased signs of airway inflammation and atopy, characterized by high IgE plasma levels and increased pulmonary cytokines, reduced frequency of lung CD4+CD25+Foxp3+ T cells, but without bronchial hyperreactivity, compared to sensitized wild type (WT) mice. Our results provide evidence that the lack of CD73 causes an un-controlled allergic sensitization, suggesting that CD73 is a key molecule at the interface between innate and adaptive immune response. The knowledge of host immune factors controlling allergic sensitization is of crucial importance and might help to find preventive intervention acting before allergy develops.